Encuentros del metro : nuevas perspectivas en la ciudad (2017)
The project centers in the Architecture as infrastructure. In which. The student realize the potential that it has as an urban integration system, in other words, the highline infrastructure becomes a space of encounters of infinite relations and, to strengthen this relations, the student proposed the idea of a market-bazaar which supports the main concept: High line encounters.--Tomado del Formato de Documento de Grado.